Criminal Procedure Code Germany and its differences FROM Criminal Procedure Code UKRAINE - Молдован, А. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
In this article the author gives a detailed description of the Criminal Procedure Code, Germany,and considering the differences and similarities between the Code of Criminal Procedure Germany and the Criminal Procedure Code of Ukraine.